Telephone Cognitive-Behavioral Therapy for Adolescents With Obsessive-Compulsive Disorder: A Randomized Controlled Non-inferiority Trial - Turner, Cynthia M. (J Am Acad Child Adolesc Psychiatry, 2014)
OBJECTIVE: Many adolescents with obsessive-compulsive disorder (OCD) do not have access to evidence-based treatment. A randomized controlled non-inferiority trial was conducted in a specialist OCD clinic to evaluate the effectiveness of telephone cognitive-behavioral therapy (TCBT) for adolescents with OCD compared to standard clinic-based, face-to-face CBT. METHOD: Seventy-two adolescents, aged 11 through 18 years with primary OCD, and their parents were randomized to receive specialist TCBT or CBT. The intervention provided differed only in the method of treatment delivery. All participants received up to 14 sessions of CBT, incorporating exposure with response prevention (E/RP), provided by experienced therapists. The primary outcome measure was the Children’s Yale–Brown Obsessive-Compulsive Scale (CY-BOCS). Blind assessor ratings were obtained at midtreatment, posttreatment, 3-month, 6-month, and 12-month follow-up. RESULTS: Intent-to-treat analyses indicated that TCBT was not inferior to face-to-face CBT at posttreatment, 3-month, and 6-month follow-up. At 12-month follow-up, there were no significant between-group differences on the CY-BOCS, but the confidence intervals exceeded the non-inferiority threshold. All secondary measures confirmed non-inferiority at all assessment points. Improvements made during treatment were maintained through to 12-month follow-up. Participants in each condition reported high levels of satisfaction with the intervention received. CONCLUSION: TCBT is an effective treatment and is not inferior to standard clinic-based CBT, at least in the midterm. This approach provides a means of making a specialized treatment more accessible to many adolescents with OCD. Clinical trial registration information–Evaluation of telephone-administered cognitive-behaviour therapy (CBT) for young people with obsessive-compulsive disorder (OCD); http://www.controlled-trials.com; ISRCTN27070832.